A fraude à execução na perspectiva da boa-fé objetiva - Cignachi, Gustavo Chies (2015)
The work seeks to defend the feasibility of an interpretation of the fraud against creditors in execution actions based on objective good faith. In the first part, it presents the historical origins of objective good faith in Private Law and defends the possibility of its adoption in Public Law. In the second part, it examines the distinction between fraud against creditors and fraud against creditors in execution actions, it demonstrates the interpretative application of objective good faith and it indicates the arising duties. In the third part, it points out certain situations and seeks solutions in interpreting the objective good faith, as well as it discuss how to defend the purchaser against the recognition of fraud